2015
DOI: 10.3324/haematol.2015.128439
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid as compared with observation in multiple myeloma patients at biochemical relapse: results of the randomized AZABACHE Spanish trial

Abstract: © F e r r a t a S t o r t i F o u n d a t i o n R. García-Sanz et al. 1208haematologica | 2015; 100(9)Myeloma Group (GEM/PETHEMA) in order to evaluate whether treatment with ZA delays the time to next therapy (TNT) in patients with MM in biochemical relapse, compared to the standard management with observation only. Methods Trial designIn 2010, GEM/PETHEMA activated the "Analysis of Zoledronic Acid therapy in MM in BioCHEmical relapses" (AZABACHE) trial. This randomized, prospective, open label, phase IV trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Our study replicates the BMA advantage in the era when most patients receive novel, highly active anti‐myeloma agents (bortezomib or lenalidomide) and lower cumulative doses of dexamethasone compared with historical practice . Other trials, conducted largely before the widespread use of bortezomib and lenalidomide, have confirmed the lower risk of SRE with BMA, whereas survival benefits have not been seen consistently . Similarly to a prior network meta‐analysis and a phase 3 trial, we did not observe differential efficacy of various BMAs, with the caveat that denosumab use was too rare to draw conclusions .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study replicates the BMA advantage in the era when most patients receive novel, highly active anti‐myeloma agents (bortezomib or lenalidomide) and lower cumulative doses of dexamethasone compared with historical practice . Other trials, conducted largely before the widespread use of bortezomib and lenalidomide, have confirmed the lower risk of SRE with BMA, whereas survival benefits have not been seen consistently . Similarly to a prior network meta‐analysis and a phase 3 trial, we did not observe differential efficacy of various BMAs, with the caveat that denosumab use was too rare to draw conclusions .…”
Section: Discussionsupporting
confidence: 82%
“…34 Other trials, conducted largely before the widespread use of bortezomib and lenalidomide, have confirmed the lower risk of SRE with BMA, whereas survival benefits have not been seen consistently. 2,4,6,35,36 Similarly to a prior network metaanalysis and a phase 3 trial, we did not observe differential efficacy of various BMAs, with the caveat that denosumab use was too rare to draw conclusions. 4,7 Early institution of BMA may be paramount to achieve benefits, as the risk of SRE peaks in the first 2 years from diagnosis and is associated with higher mortality.…”
Section: Discussionsupporting
confidence: 74%
“…Zoledronic acid is a highly effective drug that inhibits osteoclast-mediated bone resorption, and is approximately 100–1000 times more potent than other bisphosphonates [ 4 , 5 ]. Zoledronic acid has been approved for the treatment of patients with bone metastasis [ 6 , 7 ] and tumor-induced hypercalcemia [ 8 ]. Because SREs can repeatedly occur during bone metastases, the clinical guidelines of the American Society of Clinical Oncology recommend that zoledronic acid should be taken indefinitely every 3–4 weeks unless there is deterioration in the general health of patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, this issue has been evaluated in a single small study, the recently reported AZABACHE trial. In this study, zoledronic acid did not alter biochemical myeloma response, though it did significantly reduce the risk of severe skeletal complications (progressive bone disease, spinal cord compression, and hypercalcemia) as compared to the observation group, suggesting that bisphosphonates may have utility in the setting of biochemical relapse (Garcia‐Sanz et al, ), however future studies evaluating this issue are warranted. In addition, complications associated with bisphosphonate therapy, including acute phase reactions, ARONJ, renal impairment, and the concern that long‐term bisphosphonate use may result in over‐suppression of bone turnover that can induce marked skeletal fragility must be considered and weighed against the potential treatment benefits at the time that re‐initiation of bisphosphonates is considered.…”
Section: Controversies In Identification and Management Of Myeloma Bomentioning
confidence: 63%